The Influence of Physical Activity and Sedentary Behavior on Living to Age 85 Years Without Disease and Disability in Older Women. (20th November 2017) - Rillamas-Sun, Eileen; LaMonte, Michael J; Evenson, Kelly R; Thomson, Cynthia A; Beresford, Shirley A; Coday, Mathilda C; Manini, Todd M; Li, Wenjun; LaCroix, Andrea Z
Abstract: Background: Whether physical activity (PA) and sedentary behavior influence the odds of women living to age 85 years without chronic disease or disability is not well described. Methods: Participants of the Women's Health Initiative ( n = 49, 612) were categorized based on health status by age 85 years: (i) lived without developing major chronic disease or mobility disability ("healthy"); (ii) lived and developed mobility disability with or without disease; (iii) lived and developed major chronic disease, but not mobility disability; and (iv) died before their 85th birth year. Multinomial logistic regression models that adjusted for covariates such as age, race/ethnicity, and body size estimated associations of self-reported PA and sitting time on developing major disease or mobility disability or dying before age 85 relative to being healthy. Results: Mean ± SD baseline age was 70.2 ± 3.6 years. Distributions were: 22% healthy, 23% had mobility disability, 26% had major disease, and 29% died. Relative to those with high total PA, the adjusted odds ratios (OR) (confidence intervals [CI]) for mobility disability was 1.6 (1.4–1.7), 1.2 (1.1–1.3), and 1.1 (1.0–1.2) for women with no, low, and moderate total PA, respectively ( p -trend < .001). The corresponding covariate-adjusted OR (CI) for mortality was 1.7 (1.5–1.8), 1.2 (1.1–1.3), and 1.0 (1.0–1.1) ( p -trend < .001). Total PA was not associated with developing chronic disease before age 85 years. Sitting ≥10 relative to <5 hours per day increased the odds of mobility disability (1.1, CI: 1.0–1.3) and mortality (1.2, CI: 1.0–1.3) prior to age 85 years ( p < .001). Conclusions: Increasing PA to recommended levels and reducing sitting time are modifiable behaviors that may improve healthy aging in older women.